Rashba Effect in Functional Spintronic Devices - Koo, Hyun Cheol; Kim, Seong Been; Kim, Hansung; Park, Tae-Eon; Choi, Jun Woo; Kim, Kyoung-Whan; Go, Gyungchoon; Oh, Jung Hyun; Lee, Dong-Kyu; Park, Eun-Sang; Hong, Ik-Sun; Lee, Kyung-Jin (WILEY-V C H VERLAG GMBH, 2020)
Exploiting spin transport increases the functionality of electronic devices and enables such devices to overcome physical limitations related to speed and power. Utilizing the Rashba effect at the interface of heterostructures provides promising opportunities toward the development of high-performance devices because it enables electrical control of the spin information. Herein, the focus is mainly on progress related to the two most compelling devices that exploit the Rashba effect: spin transistors and spin-orbit torque devices. For spin field-effect transistors, the gate-voltage manipulation of the Rashba effect and subsequent control of the spin precession are discussed, including for all-electric spin field-effect transistors. For spin-orbit torque devices, recent theories and experiments on interface-generated spin current are discussed. The future directions of manipulating the Rashba effect to realize fully integrated spin logic and memory devices are also discussed.
Keywords: SPIN-ORBIT-TORQUE; ELECTRIC-FIELD CONTROL; PERPENDICULAR MAGNETIZATION; ATOMIC LAYERS; ANISOTROPY; DYNAMICS; SURFACE; MAGNETISM; DRIVEN; LOGIC